How to link/integrate Internet of Things and legacy IT conceptually a standards and enterprise architecture based review with expert interviews and an example - Damalie, Elorm (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Technology has always been a key element for business. Effectiveness, productivity, competitive advantage and return of investment are the most important issues for business. Within the past 20 years technological advancement has contributed immensely to business. They include among others ERP system, CRM, cloud computing, business intelligence and analytics, mobile apps and content management. Internet of things is the next phase of this technological advancement happening. It has become one of the most talked about thing in computing in recent years. Its popularity in the information technology world is growing at an incredible pace. Everyday objects will become smart objects that will be connected to internet and will communicate with each other in the near future. This will lead to the creation of new business in all areas of our lives. In this research, the main objective is conceptually integrate Internet of Things(IoT) with legacy systems. To find out the current state of legacy systems and the current state of the Internet of Things. Legacy systems and Internet of Things both have their challenges. Finding the common ground between the two will affect the business development and business processes in major ways. Legacy systems can always be improved or changed completely to a newer technology. The research will also focus on the effect an IoT integrated system will have on business processes and business models. This research will also shed light on the use of enterprise architecture in the integration process. The theoretical part of this research forms the foundation for the empirical part. The theoretical part studies the relevant literature of the topics of the research theme: Internet of things, Service Oriented Architecture (SOA), interoperability, standardisation , Enterprise Architecture(EA) and integration methods. Qualitative method of research is used in the empirical part of this thesis. Four carefully chosen experts from well established international Information technology companies and an international university are interviewed for gathering of data. The case study is to show the application of the core of this research to a real company. Based on the finding of this study, we identified SOA as the way to integrate IoT to legacy systems to derive services that add to the business value of a company. SOA played a vital role in achieving interoperability since the issues of standardisation still persist in IoT. EA is a vital to the success of this study. The study provided a better understanding of the importance and use of EA in companies.